Update on pulmonary arterial hypertension pharmacotherapy. Issue 5 (3rd July 2016) - Velayati, Arash; Valerio, Marcos G.; Shen, Michael; Tariq, Sohaib; Lanier, Gregg M.; Aronow, Wilbert S.
ABSTRACT: Pulmonary artery hypertension (PAH) refers to several subgroups of disease in which the mean pulmonary artery pressure (mPAP) is elevated to more than 25 mm Hg, pulmonary artery wedge pressure (PAWP) ≤ 15 mmHg, and an elevated pulmonary vascular resistance (PVR) > 3 Wood units as confirmed by right heart catheterization. The prevalence and geographic distribution of PAH vary depending on the type and etiology of the disease. Despite enormous efforts in the research and development of therapeutic agents in the last twenty years, the disease remains relatively incurable and the overall prognosis remains guarded. Median survival for an untreated patient is 2.8 years. In the last three decades, there have been dramatic advances in understanding the molecular mechanisms and signaling pathways involved in the disease, resulting in emerging new treatment strategies. In the following pages, we will review currently approved treatments for PAH, as well as a new generation of investigational drugs.